The Importance of Ecological and Legal Education and Training - Azizova Nilufar Farkhadovna (Global Scientific Publishing, 2025)
This article highlights the importance of ecological and legal education and training in the life of society. The role of raising the environmental awareness and legal culture of citizens in environmental protection is emphasized. Also, the priority tasks of forming ecological and legal knowledge in educational institutions, methods of education related to the study of environmental legislation and practical activities are discussed. The author emphasizes the important role of ecological education in ensuring ecological sustainability and responsibility in society. The article briefly discusses the issue of the harmony of ecological and legal education and environmental education from a scientific point of view
Keywords: Ecological and legal education; education; nature